2020
DOI: 10.3390/jcm9082445
|View full text |Cite
|
Sign up to set email alerts
|

Models Contribution to the Understanding of Sarcoidosis Pathogenesis: “Are There Good Models of Sarcoidosis?”

Abstract: Sarcoidosis is a systemic, granulomatous, and noninfectious disease of unknown etiology. The clinical heterogeneity of the disease (targeted tissue(s), course of the disease, and therapy response) supports the idea that a multiplicity of trigger antigens may be involved. The pathogenesis of sarcoidosis is not yet completely understood, although in recent years, considerable efforts were put to develop novel experimental research models of sarcoidosis. In particular, sarcoidosis patient cells were used within i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 159 publications
0
8
0
Order By: Relevance
“…As noted in a recent review of in vitro/in vivo sarcoidosis models, more innovative approaches are needed to explore the pathogenesis and pathophysiology of sarcoidosis [ 67 ]. A focus on granuloma formation alone is insufficient to provide information on mechanisms of fibrosis formation which affects some 20% of sarcoidosis patients [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…As noted in a recent review of in vitro/in vivo sarcoidosis models, more innovative approaches are needed to explore the pathogenesis and pathophysiology of sarcoidosis [ 67 ]. A focus on granuloma formation alone is insufficient to provide information on mechanisms of fibrosis formation which affects some 20% of sarcoidosis patients [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…evidence suggests that Th17 +sarcoidosis granulomas formation & maintenance. According to the popular view, antigen persistence causes inflammatory cascade intensification & prolongation (with tumor necrosis factor increase), while stoppage of the inflammatory cascade and disease remission occur following the antigen clearance [7].…”
Section: Recentmentioning
confidence: 99%
“…Animal models of sarcoidosis are difficult to induce, the previous attempts to evaluate the causes of the disease progression and the etiology-based treatment were unsuccessful ( 48 ). Animal studies have mainly demonstrated the development of pulmonary granulomas without fibrosis following exposure to various antigens ( M. Tuberculosis peptides , P. Acne , carbon nanoparticles).…”
Section: Animal Modelsmentioning
confidence: 99%
“…The granulomas observed in the experiment were shown to exist only if there was a continuous exposure to the adjuvant. We believe that sarcoidosis patients are chronically exposed by one or several triggers that contribute development and persistence of granulomas ( 48 ) or autoimmune inflammation ( 6 ).…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation